IWALEWA-HAUS, BAYREUTH (International Library of African Music, 1983)
Keeping up his eventful and multi-media calendar at Iwalewa-Haus, Bayreuth University, Wolfgang Bender has continued to sponsor the African arts in Germany with his invitation of Muraina Oyelami, Yoruba drummer, and former member of the Duro Ladipo Theatre Company (Nigeria) in 1982, Evaristo Muyinda, grand old man of Kiganda music (Uganda), the Kachamba Brothers’ Band (Malawi), Nana Danso-Abiam, Ghanaian atenteben flute player and musicologist, and John Collins, “The highlife specialist” and guitarist from Ghana, in 1983.
Keywords: African Music